Habemus doctorem?: considerações sobre processos de subjetivação no campo acadêmico contemporâneo - Silva, Mauricio Júnior Rodrigues da [UNESP] (2015)
To occupy a subject-position within a contemporary academic field, you may not just be on it, you need to follow a series of discursive and non discursive practices. Among them, having a procedure of writing, becoming a researcher, registering each of its productions, have titles, among others. These and other practices legitimize the subject in truth games that pervade this field. Against these games, we must question some of those processes by which the individual must pass to occupy a position within the academic field that enables him to enunciate truths with property. In the persuit of specifying these practices, we tried to undertake an analysis of discourse in Foucault guided arque-genealogy. Our arque-genealogy is within a field of knowledge called Discourse Analysis, developed in France in the years 60/70 through the studies of Michel Foucault and Michel Pêcheux and thought in Brazil in contemporaneity from the historical perspective of Maria do Rosário Gregolin (2002, 2004, 2006b). This theoretical tools allows us to undertake a critique of this theory, in order to check how the academic field is constructed from a relationship of forces. To discuss the subjective processes that occurs in the academic field, we took up two main axes of analysis: a first guided in the procedures of writing, from the analysis of certain manuals that establishes academic standards of writing, circulation and legitimization of texts; a second axis derived from the curriculum register, which examined the Plataforma Lattes as an important device for the subjectivity of the academic building. The analysis of these two themes enabled us to understand how the practices in this field are guided by the shared titles. They act as important instruments of power through which individuals produce their subjectivities. Bans, segregation from these shares are described in the research, especially from the separation between the Homo accademicus and Homo...